Lands of Castile : Campos de Castilla and other poems - Machado, Antonio (Aris and Phillips Hispanic Classics Ser., 2002)
Antonio Machado was born in Seville in 1885 and died in southern France early in 1939, escaping from the Nationalist advance in the Spanish Civil War. He is increasingly recognized as one of the four greatest Spanish-language poets of the twentieth century, but lack of adequate translations has limited his appreciation in the English-speaking world. Here a native Spanish and a native English speaker set out to remedy this deficiency. The beauty of his landscape, fused with its sadness as his young wifeÆs resting pace gave Machado his distinctive voice: intimate, elegiac, at once detached and involved, most characteristically expressed in Campos de Castilla (1917), from which many of the poems here selected are taken. The language of his poetry is spare, relying strongly on nouns and adjectives, asserting more than describing, equally anti-baroque and against the æexcesses of modern cosmeticsÆ (Self Portrait). His father had been a collector of folklore, and Machado saw the romance (ballad) tradition as lying at the heart of the authentic Spanish poetic tradition. English cannot recreate the assonance on which he relied, but this translation captures the essential rhythm as well as the poignancy of the original. Spanish text with facing-page translation, introduction and notes.